Midiatização e organizações: uma análise das implicações da utilização das novas tecnologias de mídias sociais como prática estratégica na comunicação de uma organização bancária - Oliveira, André Vaz de (2017)
The study starts from the premise that the social media used in the daily life of organizations has implications in its internal communication, leading to a change in the organizational landscape with effects on daily social practice, and consequently affecting and linking the strategic organizational practice. It is argued that the interaction of individuals with this technology constitutes social practices, and these practices are sustained by interaction with social media. In view of these assertions, the present study sought to analyze the implications of the use of new social media technologies, as a strategic practice in the communication of an organization of the banking sector. The institutional theory represented by the perspective of Hjarvard medialization and the strategy as a social practice of Jarzabkowski, Balogun, Seidl, was adopted as theoretical framework for process analysis. The study was a descriptiveexploratory study with an inductive approach, with a qualitative approach, with longitudinal analysis amplitude with a longitudinal approximation of 1 year. A case study was carried out on the use of social media in the strategic communication of the organization, aiming to Social media forum. The results showed that the use of social media in the strategic communication of the organization begins to influence the way in which the communication between the hierarchical levels occurs. The results also showed that, given the purpose for which social media was implemented, the daily practice of its use was manifested in a varied way. Given these results, it was concluded that, social media through affordances influences users' behavior, in the sense of this new form interaction imply in the unfolding of a new communication paradigm of the banking organization Gama.